Management of currency risks - Malysheva, Natalia (My University, 2014)
Economic risk is defined as the probability of adverse effects of exchange rate changes on the economic situation of the company, for example, reducing the likelihood of turnover or changes in prices of factors of production and finished products as compared to other prices in the domestic market. The risk may be due to changes in the severity of competition both on the part of producers of similar goods, as well as from manufacturers of other products, as well as changes in consumers' commitment to a particular brand. The impact may also have other sources, such as the government's response to changes in exchange rates or wage restraint as a result of inflation caused by currency depreciation.
Keywords: currency risks; exchange rate; валютний ризик; обмінний курс